Patterns and predictors of adherence to health-protective measures during COVID-19 pandemic in the UK: cross-sectional and longitudinal findings from the HEBECO study - Dimitra Kale; Aleksandra Herbec; Emma Beard; Natalie Gold; Lion Shahab (BMC, 2022)
Abstract Background Adherence to health-protective behaviours (regularly washing hands, wearing masks indoors, maintaining physical distancing, carrying disinfectant) remains paramount for the successful control of COVID-19 at population level. It is therefore important to monitor adherence and to identify factors associated with it. This study assessed: 1) rates of adherence, to key COVID-19 health-protective behaviours and 2) the socio-demographic, health and COVID-19-related factors associated with adherence. Methods Data were collected on a sample of UK-based adults during August-September 2020 (n = 1,969; lockdown restrictions were eased in the UK; period 1) and November 2020- January 2021 (n = 1944; second UK lockdown; period 2). Results Adherence ranged between 50-95%, with higher adherence during the period of stricter measures. Highest adherence was observed for wearing masks indoors (period 1: 80.2%, 95%CI 78.4%-82.0%, period 2: 92.4%, 95%CI 91.1%-93.6%) and lowest for carrying own disinfectant (period 1: 48.4%, 95%CI 46.2%-50.7%, period 2: 50.7%, 95%CI 48.4%-53.0%). Generalized estimating equation models indicated that key factors of greater odds of adherence included being female, older age, having higher income, residing in England, living with vulnerable individuals and perceived high risk of COVID-19. Conclusions Targeted messages to different demographic groups may enhance adherence to health-protective behaviours, which is paramount for the control of airborne respiratory diseases. Protocol and analysis plan Registration The analysis plan was pre-registered, and it is available at https://osf.io/6tnc9/ .